Death as a Transition to the New Reality. Nouveau Approach of the Court in the Light of the Dies Irae Lucjan Rydel - Muszyńska, Justyna (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
Death is the natural end of life. Everything that was born must die eventually, “absent from the bodyand face to the Lord” as about the death Saint Paul writes. The soul is separated from the body. Theyconnect with him again on a ‘resurrection of the dead’.Undoubtedly, death is a passage to another reality, a world intangible. World where the court waitsfor us the judgment and three ways: hell, purgatory and heaven — the Heavenly Jerusalem at the endof time.This perspective is accompanied by the Christian meaning of death and its consequences.The most complete picture of what is after death, shows the Apocalypse of St. John. This book closesthe canonical collection of books of the New Testament.The Apocalypse was a source of inspiration for many artists. However, the most intensive exploitationcan by noticed in the crucial period of notice of Young Polish.One of the writers who uses its rich symbolism and links was Lucjan Rydel.It is part of the vision of the end of the world which marks the end of the civilization XIX century. Itshows various social groups, bringing something home that the Court affects everyone. Gradual changesin the natural world, preach Day of Wrath. Rydel shows in its mystery person closely associated with theChristian religion, the Pope — the head of the Church and Elijah — the prophet of the Old Testament.Thus fits its vision in a relation of the religious circle. Leviathan heralds the advent of a final battlebetween good and evil. Despite the death of positive heroes of the work, the Pope and Elijah, killed bythe forces of evil, ending Mystery gives hope. We see the Mother of Mercy, Our Lady defending scaredpeople. In Rydel’s Dies irae the judge is Jesus Christ, the good and compassionate, understanding attitudeof people, absolving, listening to his Mother.